Strategi Komunikasi Instagram Hybool Dalam Pemasaran Wedding Fotografi - Aris Darmawan, Moch Djauhari (DIGICOM : Jurnal Komunikasi dan Media, 2022)
This research departs from the objective reality, namely the massive use of Instagram media as a medium in promoting business, in this case, the researcher sees a social phenomenon, namely about the marketing communication strategy carried out by one of the wedding photography business fields, namely Hybool, which utilizes Instagram media in promote their photography services. In carrying out a marketing communication strategy, Hybool uses Instagram as a basis for introducing its online wedding photography services to its target consumers, the majority of whom are young people. Therefore, the researcher focused on how the communication strategy developed by Hybool in marketing its services on Instagram. Then, in conducting this research, the researcher chose to use a descriptive qualitative research method. This, the researchers chose because it was in accordance with the object to be studied, namely analyzing the marketing communication strategy carried out by Hybool on Instagram, as well as the data that the researchers got from the results of observations, interviews, and also documentation. Hybool itself has proven to be effective in conducting marketing communications on Instagram, this is known from the continued increase in revenue year after year and is also consistent. In this case, because Hybool itself has succeeded in effectively utilizing the advantages that exist on Instagram, in the form of many features that support promotions, thus making potential consumers interested in Hybool wedding photography services